Pengaruh Keterlibatan Stakeholder dan Inovasi Teknologi Terhadap Pengembangan Kurikulum Pendidikan TNI AL - Akbar Dharmawan (Jurnal Multidisiplin Indonesia, 2024)
The development of the education curriculum in the Indonesian Navy faces challenges in adapting to actual needs and technological advances. Stakeholder involvement and technological innovation are considered key factors in improving curriculum quality, but their impact on the development of the Indonesian Navy curriculum is not fully understood. This study aims to evaluate the influence of stakeholder involvement and technological innovation on the development of the Indonesian Navy education curriculum. The method used is quantitative research by collecting data through surveys to various related stakeholders, including members of the Indonesian Navy, teachers, and industry representatives. Validity tests show that all questions are valid with Corrected Item Total Correlation values ​​between 0.68 and 0.80, while reliability tests show Cronbach's Alpha values ​​for the variables of stakeholder involvement, technological innovation, and curriculum development of 0.85, 0.88, and 0.82, respectively, indicating good internal consistency. The linear regression results show that the regression coefficient for stakeholder involvement is 0.45 (t = 3.75, p = 0.000) and for technological innovation is 0.60 (t = 5.45, p = 0.000), both of which are statistically significant. The ANOVA test produces an F-statistic of 12.30 with a p-value of 0.000, indicating that the overall regression model is significant in explaining variations in curriculum development. This study concludes that stakeholder involvement and the application of technological innovation have a significant impact on the development of the Indonesian Navy education curriculum.